2021
DOI: 10.7554/elife.73682
|View full text |Cite
|
Sign up to set email alerts
|

Urgency forces stimulus-driven action by overcoming cognitive control

Abstract: Intelligent behavior requires to act directed by goals despite competing action tendencies triggered by stimuli in the environment. For eye movements, it has recently been discovered that this ability is briefly reduced in urgent situations (Salinas et al., 2019). In a time-window before an urgent response, participants could not help but look at a suddenly appearing visual stimulus, even though their goal was to look away from it. Urgency seemed to provoke a new visual–oculomotor phenomenon: A period in which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Work by Poth, 2021 showed that robust capture phenomena can be generated in urgent tasks that use button presses instead of saccades and impose very different cognitive demands on the choice process. Task conditions akin to pro and anti were distinguished not by different spatial rules, but rather by contextual features that could be congruent (e.g., >>>>>) or incongruent with a central stimulus (e.g., <<><<).…”
Section: Discussionmentioning
confidence: 99%
“…Work by Poth, 2021 showed that robust capture phenomena can be generated in urgent tasks that use button presses instead of saccades and impose very different cognitive demands on the choice process. Task conditions akin to pro and anti were distinguished not by different spatial rules, but rather by contextual features that could be congruent (e.g., >>>>>) or incongruent with a central stimulus (e.g., <<><<).…”
Section: Discussionmentioning
confidence: 99%
“…Vagal tone measured at rest is associated with connectivity between the DMN and FPN (Chand et al, 2020). The transition between cognitive processes can either be subject to self-regulated metacognitive control (Shimamura, 2014) or stimulus-driven as a result of stress and emotional influence (Baek & Falk, 2018;Poth, 2021). A recent study found that the FPN was involved in metacognitive judgements along with DMN structures, where activity in both the DLPFC and MPFC was negatively associated with confidence judgements (Morales et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The DLPFC is specifically involved in metacognitive decision-making, while both DLPFC and MPFC are involved in prospective metacognitive judgments (Fleur et al, 2021;Vaccaro & Fleming, 2018). Cognitive processes can go from being metacognitively controlled (Friedman & Robbins, 2022;Shimamura, 2014) to reactive (stimulus-driven) when subjected to stress or under emotional influence (Baek & Falk, 2018;Poth, 2021). Previous studies on CyOs identified several emotional processes that may have differing effects on teamwork and communication (Ask et al, 2021b;Lugo et al, 2016Lugo et al, , 2017bLugo et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that alerting is driven by the locus coeruleus-norepinephrine system which is responsible for maintaining an adequate level of arousal (Aston-Jones & 12 Dietze and Poth Journal of Cognition DOI: 10.5334/joc.242 Cohen, 2005). The activity of the locus coeruleus-norepinephrine system has been associated with different modes (tonic and phasic;Aston-Jones & Cohen, 2005;Gabay et al, 2011;Gabay & Henik, 2010) as reflected by pupillary responses through state changes of phasic alertness (Petersen et al, 2017) and urgency (Poth, 2021). This in turn has been found to influence the appearance of inhibition of return, a common phenomenon of spatial orienting (Gabay et al, 2011), which demonstrates that both networks can interact.…”
Section: Discussionmentioning
confidence: 99%